Specification of a model for The study of entrepreneurial Migratory flows - Bolivar Mojica, Eyder; Bustos-Aguayo, José Marcos; García Lirios, Cruz (Cinzontle, 2019)
The specification of a model for the study of entrepreneurial migratory flows in a town in central Mexico was the objective of this work. A documentary, retrospective and exploratory study was carried out with a selection of sources indexed to international repositories, considering the period of publication from 2000 to 2019. A model was specified in which it was possible to notice two entrepreneurial styles, one focused on the optimization of resources and another focused on process innovation. The study design limited the findings to the literature consulted, suggesting the extension of the work other repositories.